Pengaruh Cash Ratio Dan Debt To Asset Ratio Terhadap Return On Equity Pada Lembaga Keuangan Desa (LKD) Abhinaya Lestari Kecamatan Panjalu Periode 2020-2022 - Haryati, Sani; Amirah Makarim, Siti (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
The aim of this research is to understand the impact of Cash Ratio and Debt to Asset Ratio on Return On Equity in the Abhinaya Lestari Village Financial Institution (LKD) during the period 2020-2022. The approach used is quantitative descriptive, and the data analysis technique applied is Multiple Regression Analysis. The research findings indicate that the study meets the classical assumption tests. From the multiple linear analysis, the equation Y = 1.032 + 1.932 X1 + 0.103 X2 + e is derived. The Coefficient of Determination (R2) of 0.255 indicates that Cash Ratio and Debt to Asset Ratio collectively influence Return On Equity by 25.5%, while the other variables not included in this study affect the remaining 74.5%. Partial tests reveal that Current Ratio significantly affects Return On Equity, with a t value of (3.120) > t table (2.032) and a significance of 0.025 < 0.05, thus accepting Ha and rejecting H0. Similarly, Debt To Asset Ratio also significantly affects Return On Equity, with a t value of (3.457) > t table (2.032) and a significance of 0.002 < 0.05, leading to the acceptance of Ha and rejection of H0. Simultaneous tests show that the F value of (6.984) > F table (3.280) with a significance of 0.03 < 0.05, therefore accepting Ha and rejecting H0. Hence, it can be concluded that both Current Ratio and Debt to Asset Ratio have a significant influence on Return On Equity, both partially and simultaneously.